Social media data extraction and content analysis - Hai-Jew, Shalin (Advances in Data Mining and Database Management (ADMDM) Book Series, 2017)
Explores various social networking platforms and the technologies being utilized to gather and analyse information being posted to these venues. Highlighting emergent research, analytical techniques, and best practices in data extraction in global electronic culture, this publication is an essential reference source for researchers, academics, and professionals